Analysis of Language Errors in Scientific Works of Thailand Students at UIN Raden Mas Said Surakarta: A Syntactic Review Based on Characteristics of Effective Sentences - Clarisa Titania Pangestika; Mifta Umi Alfi Atur Rohmaniah; Salwa Halimatus Sa'diyah; Anavee Khoona (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
This study aims to identify and analyze syntactic errors in the scientific papers of Thai students at the Raden Mas Said State Islamic University (UIN) Surakarta. As foreign speakers, Thai students often experience first language (L1) interference when writing in Indonesian, which causes various errors at the syntactic level. This study uses a qualitative descriptive approach. Data were obtained through documentation of Thai students' scientific papers collected purposively. The data analysis technique was carried out by identifying, classifying, and interpreting forms of syntactic errors based on seven characteristics of effective sentences: equivalence, parallelism, assertiveness, economy, accuracy, cohesion, and logic. The results of the analysis show that students still make various syntactic errors in all of these aspects. The main causes of errors include differences in the structure of Indonesian and Thai languages and lack of mastery of formal language rules. These findings are expected to be used as evaluation material in teaching Indonesian for Foreign Speakers (BIPA), especially in academic writing. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis kesalahan sintaksis dalam karya ilmiah mahasiswa asal Thailand di Universitas Islam Negeri (UIN) Raden Mas Said Surakarta. Sebagai penutur asing, mahasiswa Thailand kerap mengalami interferensi bahasa pertama (L1) saat menulis dalam bahasa Indonesia, yang menyebabkan berbagai kesalahan pada tataran sintaksis. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data diperoleh melalui dokumentasi karya ilmiah mahasiswa Thailand berupa makalah dan tugas akhir mata kuliah yang dikumpulkan secara purposive. Teknik analisis data dilakukan dengan cara mengidentifikasi, mengklasifikasikan, dan menginterpretasikan bentuk-bentuk kesalahan sintaksis berdasarkan tujuh ciri kalimat efektif, yaitu: kesepadanan, keparalelan, ketegasan, kehematan, kecermatan, kepaduan, dan kelogisan. Hasil analisis menunjukkan bahwa mahasiswa masih melakukan berbagai kesalahan sintaksis pada seluruh aspek tersebut. Faktor utama penyebab kesalahan meliputi perbedaan struktur bahasa Indonesia dengan bahasa Thai serta kurangnya penguasaan terhadap kaidah kebahasaan formal. Temuan ini diharapkan dapat menjadi bahan evaluasi dalam pengajaran bahasa Indonesia bagi penutur asing (BIPA), khususnya dalam penulisan akademik.